Complete genome sequence of the plant pathogen Ralstonia solanacearum strain ciat-078, isolated in Colombia, obtained using Oxford Nanopore Technology - López Alvarez, Diana; Leiva Sandoval, Ana Maria; Barrantes, Israel; Pardo, Juan Manuel; Dominguez, Viviana; Cuéllar, Wilmer Jose (American Society for Microbiology, 2020)
Moko is one of the main diseases affecting banana and plantain in Colombia. Here, we report the genome sequence of the causal agent, the bacterium Ralstonia solanacearum (Smith) strain CIAT-078, collected in 2004 from affected plantains in central-west Colombia. The assembled genome was obtained using Oxford Nanopore Technology.